ANALISIS KUALITAS MIKROBIOLOGI SUMBER AIR MINUM (AIR SUMUR) MASYARAKAT KOTA MATARAM SEBAGAI LANGKAH PREVENTIF TERHADAP WABAH DIARE DAN KOLERA - Muliadi, Agus; Arjun, Mursalin Arifin (Bioscientist : Jurnal Ilmiah Biologi, 2015)
Water is an essential material in life and none of the creatures in this world who do not need and do not contain water. In line with the progress and improvement of living standards, the City of Mataram have water supplies are slowly getting polluted. This study aims to: 1) To Know the value MPN Coliform, value MPN Coliform fecal and the number of colonies of Escherichia coli in the well water community in Mataram. This study is a survey research with a quantitative descriptive design. Results of this study are (1) Water wells containing Mataram City community MPN Coliform most value lower by 20 cells/100 ml, while the highest is at ≥24.000 cells/100ml; MPN Coliform fecal values were lowest at 14 cells/100 ml, while the highest is at ≥24.000 cells/100ml; while the presence of Escherichia coli bacteria positive in all samples of well water; (2) Water wells Mataram City community Based MPN Coliform indicator value is known by 75% is not suitable for consumption; indicators of MPN Coliform fecal is not worth as much as 70.8% of consumption; indicator bacteria Escherichia coli as much as 100% unfit for consumption.